The Far Nasal Part of the Visual Field - Part I - Lešták, J; Fůs, M; Lešták, T; Pitrová, Š (Česká a slovenská oftalmologie, 2023)
The aim of the study was to determine the limits of the far nasal part of the visual field. Visual field examination was performed in 15 healthy subjects (30 eyes), specifically nine women aged 20-43 years and six men aged 22-35 years. All eyes were found to have physiological ocular findings and visual acuity of 1.0 with correction less than or equal to 3 diopters. The visual field was examined with a Medmont M700 instrument by shifting the fixation point 40 degrees temporally and simultaneously turning the head nasally, with a spatial accommodation program. A total of 89 examination points were included using flicker stimuli. The far nasal limit of the visual field reached 100° in 13.3% of eyes, 105° in 20% of eyes and up to 110° in 66.7% of eyes. The limit of the far nasal part of the field of vision reached 100-110 degrees (when nose shielding was eliminated).